EXPERIÊNCIA DE IMPLANTAÇÃO DA GESTÃO POR COMPETÊNCIAS EM INSTITUIÇÃO PÚBLICA BRASILEIRA. O OUTRO LADO DA MOEDA: A OPINIÃO DOS FUNCIONÁRIOS. - Carvalho, Mauricio Moreira de (2006)
In the present globalized world, constant changes on the competitive environment constitute a dire threat to organizations' survival. The lack of strategic programs, which comprise organizational goal achievements so as to give sustainability to the organizations, contributes to the jeopardy of their effectiveness and to their competitive loss. In the case of Public Organization Management, the potential risk is credibility gap and consequent disbandment. The focus of this study is the management of public organizations, and it aims at answering intrinsic issues from one of this organization's Competence Management implementation process. Within it, the Change Management stages are assessed and actions are presented. The organization employees' opinion is used to identify restrictive and encouraging forces which influence the effectiveness of the Competence Management. The case-study method and literature review are structural elements of the adopted strategy of research. Questionnaires were used to collect data among employees of the organization under survey.